Usability Testing pada Website Politeknik Negeri Bali Menggunakan Metode System Usability Scale - Ni Nyoman Harini Puspita (Universitas Ngeri Malang, 2023)
Bali State Polytechnic (PNB) WEB is a digital information service provided by the Bali State Polytechnic campus which is open to the public at pnb.ac.id. Usability testing is carried out with the aim of knowing the quality of information services from the web user's point of view. Usability is a type of qualitative analysis to determine the quality of information systems from the point of view of ease of use by users. This study aims to carry out usability analysis on the PNB web using the System Usability Scale (SUS) method. Respondents from this study were students, lecturers, and the wider community. Data was collected using probability sampling technique by distributing questionnaires. The data analysis method is a qualitative descriptive analysis method. The usability test results show that most respondents use and utilize this web quite well. The result of the test value with the SUS technique is 60.56. The acceptability range web category of the Bali State Polytechnic has not been well received by users, while it has received grade C on the grade scale. The conclusion of this study is that the PNB website still needs improvement so that users can use it easily in searching for information so that it can be used as a tool for publishing information, profiles, facilities and services provided by the PNB campus. WEB Politeknik Negeri Bali (PNB) merupakan layanan informasi digital yang disediakan oleh kampus Politeknik Negeri Bali yang bersifat terbuka untuk umum dengan alamat pnb.ac.id. Usability testing ini dilakukan dengan tujuan untuk mengetahui kualitas layanan informasi dari sisi pengguna web. Usability merupakan jenis analisis kualitatif untuk menentukan kualitas sistem informasi dari sudut pandang kemudahan penggunaan oleh pengguna. Penelitian ini bertujuan untuk memelakukan analisis usability pada web PNB dengan mengunakan metode System Usability Scale (SUS). Responden dari penelitian ini adalahk mahasiswa, dosen, dan masyarakat luas. Data dikumpulkan dengan menggunakan Teknik probability sampling dengan menyebarkan kuisioner. Metode analisis data adalah metode analisis deskriptif kualitatif. Hasil pengujian usability menunjukkan bahwa mayoritas responden menggunakan dan memanfaatkan web ini dengan cukup baik. Hasil nilai pengujian dengan Teknik SUS adalah 60,56. Kategori acceptability range web Politeknik Negeri Bali belum diterima denan baik oleh pengguna, sedangkan mendapat grade C pada grade scale. Kesimpulan penelitian ini adalah bahwa web PNB ini masih memerlukan perbaikan agar pengguna dapat menggunakan dengan mudah dalam mencari informasi sehingga dapat dijadikan sebagi alat publikasi informasi, profile, fasilitas dan layanan yang disediakan oleh kampus PNB.